2022
DOI: 10.3389/fmicb.2022.1009297
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and abundance of antibiotic resistance genes and their relationship with nutrients and land use of the inflow rivers of Taihu Lake

Abstract: Taihu Lake is the third largest freshwater lake in China and an important source for drinking water, flood protection, aquaculture, agriculture, and other activities. This lake is connected to many principal and small rivers with inflow from west and outflow on the eastern side of the lake and these inflow rivers are believed to significantly contribute to the water pollution of the lake. This study was aimed at assessing the diversity and abundance of antibiotic resistance genes (ARGs) and mobile genetic elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Water physicochemical and microbiological characteristics at the selected sampling locations in the summer and winter of 2020 are shown in Supplementary Figure S3. Results for the spring and summer of 2019 have been reported previously (Fernanda et al, 2022). Two-way ANOVA showed that all parameters except water temperature (WT) showed spatial differences between rivers, while all parameters except chlorophyll a showed significant seasonal variation (Supplementary Table S2).…”
Section: Water Quality Analysessupporting
confidence: 72%
See 1 more Smart Citation
“…Water physicochemical and microbiological characteristics at the selected sampling locations in the summer and winter of 2020 are shown in Supplementary Figure S3. Results for the spring and summer of 2019 have been reported previously (Fernanda et al, 2022). Two-way ANOVA showed that all parameters except water temperature (WT) showed spatial differences between rivers, while all parameters except chlorophyll a showed significant seasonal variation (Supplementary Table S2).…”
Section: Water Quality Analysessupporting
confidence: 72%
“…The filters were kept at −20 °C until they were used for DNA extraction using the PowerSoil DNA Isolation Kit (MoBio Inc., Carlsbad, CA) according to the manufacturer's instructions. This kit and procedure were used in our previous studies (Vadde et al, 2019b;Fernanda et al, 2022). At least three DNA extracts were prepared for each location and season.…”
Section: Dna Extractionmentioning
confidence: 99%
“…To survey a broad range of genes, we also used a second method, which is a relative quantification method on a HT-qPCR platform. This method has recently been used by numerous studies (Muurinen et al, 2021;Fernanda et al, 2022;Flater et al, 2022;Kasuga et al, 2022;Mware et al, 2022;Samanta et al, 2022) because it allows for simultaneous presence/absence detection of numerous genes (Stedfeld). HT-qPCR is also limiting in the volume of each reaction (6.7 x 10 -3 mL vs 2 mL in conventional qPCR), which directly influences its detection limits.…”
Section: Discussionmentioning
confidence: 99%
“…A format for amplification of 384 ARGs in 5184 qPCR assays, including MGEs, were developed in 2012 [ 18 ]. The high throughput (HT) qPCR method has been widely used for a comprehensive profiling of ARGs in aquatic environments [ 19 - 23 ]. With newly discovered ARGs such as variants of mcr , a new primer set was published in 2018 [ 24 ], covering most of the classes of ARGs and MGEs.…”
Section: Advancement Of Methodologies For Args Detectionmentioning
confidence: 99%